Answer:
x=16
Step-by-step explanation:
multiply both sides of the equation by 2
multiply the number
reduce the number
Answer:
Step-by-step explanation:
2x(-5x-3)
2x(-5x)= -10x and 2x(-3)= -6x
= -10x sq - 6x
-10x is sq bc you are multiplying the same variable twice
The value of the expression in the form a(x+b)^2 is 1.5(x+2)^2 - 4
<h3>Vertex Form of a quadratic expression</h3>
Given the quadratic expressions
1.5x^2+6x+......
1.5(x^2 + 4x)
Using the completing the square method
The coefficient of x = 4
Half of the coefficient = 4/2 = 2
The square of the result = 2^2 = 4
The equation is expressed as:
f(x) = 1.5(x^2+4x+ 4) - 4
f(x) = 1.5(x+2)^2 - 4
Hence the value of the expression in the form a(x+b)^2 is 1.5(x+2)^2 - 4
Learn more on completing the square method here: brainly.com/question/1596209